Once Upon a Time: A Semiotic Analysis of Business Advertisements in Hayat Magazine - Hale Eda Akduru (Yönetim ve Organizasyon Araştırmaları Dergisi)
The 1970s are important in the history of advertising due to the introduction of multiple advertising tools. It is known that advertisements in this period were designed as a reflection of social life. The economic, political and social turmoil and transformations in the country were reflected in the practices of businesses in the 1970s, and the efforts of businesses to adapt to these changes also determined the direction of advertisements. In this study, it is aimed to determine the business dynamics of the relevant period by conducting a semiotic analysis of the most frequent advertisements in Hayat Mecmuası in 1974.